1987
DOI: 10.1099/0022-1317-68-1-123
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Evidence for the Oligomeric Arrangement of Bovine Rotavirus Nucleocapsid Protein and Its Possible Significance in the Immunogenicity of This Protein

Abstract: SUMMARYThe nucleocapsid protein of bovine rotavirus was shown to exist in trimeric units in both the virus particle and in infected cells, with the subunits linked by non-covalent interactions. These trimeric units complex further by disulphide bridges into larger units which may represent the hexameric structures observed by electron microscopy. Visualization of various nucleocapsid protein complexes was also achieved on polyacrylamide gels by treating virus preparations with urea at 37 °C or boiling in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…When the immunoprecipitates of vv-Wa-6-infected cells were incubated at 37 °C, the monomeric form of VP6 observed in boiled samples (lane 1) disappeared and a product of high molecular mass was detected (lane 2). This band of about 140 kDa corresponds to the trimeric form of VP6 (Sabara et al, 1987). This result demonstrated that the expressed VP6 was in its native conformation.…”
mentioning
confidence: 49%
“…When the immunoprecipitates of vv-Wa-6-infected cells were incubated at 37 °C, the monomeric form of VP6 observed in boiled samples (lane 1) disappeared and a product of high molecular mass was detected (lane 2). This band of about 140 kDa corresponds to the trimeric form of VP6 (Sabara et al, 1987). This result demonstrated that the expressed VP6 was in its native conformation.…”
mentioning
confidence: 49%
“…140K (Fig. 3, 4) which corresponds to the trimeric form of VP6 (Gorziglia et al, 1985;Sabara et al, 1987). Fig.…”
Section: ) Bovinementioning
confidence: 99%
“…The major inner capsid protein of rotaviruses, p45K (Novo & Esparza, 1981), also referred to as VP6 (Espejo et al, 1981;Ericson et al, 1982) is present in the virion in an oligomeric, possibly trimeric form (Gorziglia et al, 1985;Sabara et al, 1987). VP6 is an important component of the virion not only because of its abundance, accounting for approximately 80 ~ of viral protein, but also because of its constituent antigenic sites.…”
Section: Introductionmentioning
confidence: 99%
“…1 a). Omitting the heating step, an additional polypeptide of approximately 135K appears which replaces VP6 and corresponds to its trimeric form (Gorziglia et al, 1985;Sabara et al, 1987). In immunoblots nine of the 10 MAbs described and the subgroup I reference MAb recognized the trimeric but not the monomeric form of VP6 (Fig.…”
mentioning
confidence: 99%